Asiatic acid and maslinic acid protected heart via anti-glycative and anti-coagulatory activities in diabetic mice. Issue 9 (2nd September 2015) - Hung, Yi-chih; Yang, Hui-ting; Yin, Mei-chin
<x xml:space="preserve">Abstract</x> The cardiac protective effects of asiatic acid (AA) and maslinic acid (MA) in diabetic mice were examined.